Elderly School and Family Resilience: A Case Study of the BKKBN Program in Jambi Province - Indriani, Anik; Taridi, Muhamad; Angraini, Peppy; M, Irham; Ningsih, Ramadhan (Jurnal Educative: Journal of Educational Studies, 2024)
The Elderly School Program in Jambi Province addresses the growing needs of an aging population by providing continuous education and training to enhance their quality of life. While there is a growing demand for resources to support the elderly, significant gaps remain in accessibility and participation across all segments of the elderly population. This study aims to evaluate the effectiveness of the Elderly School Program, specifically its impact on elderly well-being and family resilience. Using a case study methodology, the research involved direct observation, in-depth interviews, and document analysis to assess program implementation. Findings reveal significant improvements in the knowledge, skills, and self-confidence of the elderly, alongside positive impacts on family resilience. The study contributes to the understanding of how structured educational programs can support the elderly and strengthen family bonds, offering recommendations for expanding program reach, enhancing collaboration, and developing relevant educational content. Program Sekolah Lansia di Provinsi Jambi menangani kebutuhan populasi lanjut usia yang semakin meningkat dengan memberikan pendidikan dan pelatihan berkelanjutan untuk meningkatkan kualitas hidup mereka. Meskipun ada permintaan yang meningkat untuk sumber daya yang mendukung lansia, terdapat kesenjangan signifikan dalam aksesibilitas dan partisipasi di semua segmen populasi lansia. Penelitian ini bertujuan untuk mengevaluasi efektivitas Program Sekolah Lansia, khususnya dampaknya terhadap kesejahteraan lansia dan ketahanan keluarga. Dengan menggunakan metode studi kasus, penelitian ini melibatkan observasi langsung, wawancara mendalam, dan analisis dokumen untuk menilai pelaksanaan program. Temuan menunjukkan peningkatan signifikan dalam pengetahuan, keterampilan, dan kepercayaan diri lansia, serta dampak positif terhadap ketahanan keluarga. Penelitian ini memberikan kontribusi pada pemahaman tentang bagaimana program pendidikan terstruktur dapat mendukung lansia dan memperkuat ikatan keluarga, serta menawarkan rekomendasi untuk memperluas jangkauan program, meningkatkan kolaborasi, dan mengembangkan konten pendidikan yang relevan.